2012
DOI: 10.1364/oe.20.023339
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable mid-infrared quantum cascade lasers using sampled grating reflectors

Abstract: We demonstrate a three-section, electrically pulsed quantum cascade laser which consists of a Fabry-Pérot section placed between two sampled grating distributed Bragg reflectors. The device is current-tuned between ten single modes spanning a range of 0.46 μm (63 cm(-1)), from 8.32 to 8.78 μm. The peak optical output power exceeds 280 mW for nine of the modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…However, these techniques are limited by either complex experimental arrangements [5], low power emission [6,7], the need for complex design algorithms [8], or slow condensation/evaporation processes [9]. While tunability has also been demonstrated using sampled gratings at optical [11] and mid-infrared frequencies [12], the longer wavelengths in the THz region dictate that such single-cavity devices would scale to be several tens of millimeters long, and would suffer from excessive electrical heating. To date no technique has been demonstrated that enables THz QCLs to be tuned rapidly over a wide bandwidth without loss of output power.…”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques are limited by either complex experimental arrangements [5], low power emission [6,7], the need for complex design algorithms [8], or slow condensation/evaporation processes [9]. While tunability has also been demonstrated using sampled gratings at optical [11] and mid-infrared frequencies [12], the longer wavelengths in the THz region dictate that such single-cavity devices would scale to be several tens of millimeters long, and would suffer from excessive electrical heating. To date no technique has been demonstrated that enables THz QCLs to be tuned rapidly over a wide bandwidth without loss of output power.…”
Section: Introductionmentioning
confidence: 99%
“…15 We note that single-mode operation of tunable QCLs based on sampled gratings is very challenging and the side mode suppression ratio in these devices is typically worse than 10-20 dB. 16,17 In this report, we follow the QCL array approach, first demonstrated for monolithic mid-IR tuners, 18 to produce monolithic THz source with continuous spectral tuning from 1.9 to 3.9 THz. We integrate 10 monolithic THz DFG-QCL tuners described in Ref.…”
mentioning
confidence: 99%
“…Since the conditions of wavelength resonant and phase matching are very sensitive to Δ(N eff Λ), temporal and spatial stability of the material index become more important (see also discussion below). The introduction of a tunable phase shift waveguide area will be available for this issue, which is considered as a study in the next stage [32]. Fig.…”
Section: Resultsmentioning
confidence: 99%